The effect of the evergrande bankruptcy on Chinese real estate listed firms - Martins, António Miguel Valente (2024)
The objective of the study is to examine the intra-industry effects of Evergrande’s bankruptcy on the Chinese real estate listed firms. Based on an event study, we evidence a negative and statistically significant stock price reaction to Evergrande’s bankruptcy announcement. These results are consistent with the contagion effect. We also find the highest negative impact on real estate firms with greater leverage and a higher similarity in cash flows with the bankrupt firm. Finally, the magnitude of the stock market reaction to Evergrande’s bankruptcy is reinforced or mitigated by firm-specific determinants such as size and liquidity.